CLDN1 silencing suppresses the proliferation and migration of airway smooth muscle cells by modulating MMP14 - Wei Li; Linyan Liu; Ming’ai Duanqing; Xiaoqing Xiong; Dejian Gan; Jin Yang; Mingya Wang; Min Zhou; Jun Yan (Autoimmunity, 2023)
AbstractAirway remodeling is an important pathologic factor in the progression of asthma. Abnormal proliferation and migration of airway smooth muscle cells (ASMCs) are important pathologic mechanisms in severe asthma. In the current study, claudin-1 (CLDN1) was identified as an asthma-related gene and was upregulated in ASMCs stimulated with platelet-derived growth factor BB (PDGF-BB). Cell counting kit-8 and EdU assays were used to evaluate cell proliferation, and transwell assay was carried out to analyze cell migration and invasion. The levels of inflammatory factors were detected using enzyme-linked immunosorbent assay. The results showed that CLDN1 knockdown inhibited the proliferation, migration, invasion, and inflammation of ASMCs treated with PDGF-BB, whereas overexpression of CLDN1 exhibited the opposite effects. Protein-protein interaction assay and co-immunoprecipitation revealed that CLDN1 directly interacted with matrix metalloproteinase 14 (MMP14). CLDN1 positively regulated MMP14 expression in asthma, and MMP14 overexpression reversed cell proliferation, migration, invasion, and inflammation induced by silenced CLDN1. Taken together, CLDN1 promotes PDGF-BB-induced cell proliferation, migration, invasion, and inflammatory responses of ASMCs by upregulating MMP14 expression, suggesting a potential role for CLDN1 in airway remodeling in asthma.